Economic Evaluation and Budget Impact Analysis of Vaccination against Haemophilus influenzae Type b Infection in Thailand - Kotirum, Surachai; Muangchana, Charung; Techathawat, Sirirat; Dilokthornsakul, Piyameth; Wu, David Bin-Chia; Chaiyakunapruk, Nathorn (Frontiers in Public Health, 2017)
Current study aimed to estimate clinical and economic outcomes of providing the Haemophilus influenzae type b (Hib) vaccination as a national vaccine immunization program in Thailand. A decision tree combined with Markov model was developed to simulate relevant costs and health outcomes covering lifetime horizon in societal and healthcare payer perspectives. This analysis considered children aged under 5 years old whom preventive vaccine of Hib infection are indicated. Two combined Hib vaccination schedules were considered: 3-dose series (3+0) and 3-dose series plus a booster does (3+1) compared with no vaccination. Budget impact analysis was also performed under Thai government perspective. The outcomes were reported as Hib-infected cases averted and incremental cost-effectiveness ratios (ICERs) in 2014 Thai baht ($) per quality adjusted life year (QALY) gained. In base-case scenario, the model estimates that 3,960 infected cases, 59 disability cases, and 97 deaths can be prevented by national Hib vaccination program. The ICER for 3+0 schedule was THB 1,099 ($34) per QALY gained under societal perspective. The model was sensitive to pneumonia incidence among aged under 5 years old and direct non-medical care cost per episode of Hib pneumonia. Hib vaccination is very cost-effective in the Thai context. The budget impact analysis showed that Thai government needed to invest an additional budget of 110 ($3.4) million to implement Hib vaccination program. Policy makers should consider our findings for adopting this vaccine into national immunization program.